2020
DOI: 10.21577/0103-5053.20190266
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and in vitro, in vivo and in silico Anti-Inflammatory Studies of the Novel Hybrid Based on Ibuprofen and 3-Hydroxy-Copalic Acid Isolated from Copaiba Oil (Copaifera multijuga)

Abstract: A novel anti-inflammatory hybrid 3-ibuprofenyl-copalic acid (3-IbuCA) was synthesized from 3-hydroxy-copalic acid isolated from Amazonian copaiba oil (Copaifera multijuga Hayne), and the anti-inflammatory ibuprofen. After full characterization, several assays to verify its anti-inflammatory effects were performed in vitro, in vivo and in silico (molecular docking). Induced fit docking was performed to observe the interactions with the enzymes cyclooxygenase-1 (COX-1) and cyclooxygenase-2 (COX-2). In vitro test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The literature shows many reports on functional copaiba oil-based NE with remarkable anti-Leishmania (Dhorm Pimentel de Moraes et al, 2018), larvicidal (Rodrigues et al, 2014), antiinflammatory (Lucca et al, 2018) and antimicrobial (Vaucher et al, 2015) activities. Moreover, the in vivo biocompatibility of copaiba oil was already reported in mice and rats (Alvarenga et al, 2020;Souza et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The literature shows many reports on functional copaiba oil-based NE with remarkable anti-Leishmania (Dhorm Pimentel de Moraes et al, 2018), larvicidal (Rodrigues et al, 2014), antiinflammatory (Lucca et al, 2018) and antimicrobial (Vaucher et al, 2015) activities. Moreover, the in vivo biocompatibility of copaiba oil was already reported in mice and rats (Alvarenga et al, 2020;Souza et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
“…Copaiba oil is found in Central and Western Amazonia. It is composed of a mixture of triglycerides and fat acids (Ribeiro et al, 2017b), among which copalic acid is the major compound (Souza et al, 2020). The literature shows many reports on functional copaiba oil-based NE with remarkable anti-Leishmania (Dhorm Pimentel de Moraes et al, 2018), larvicidal (Rodrigues et al, 2014), antiinflammatory (Lucca et al, 2018) and antimicrobial (Vaucher et al, 2015) activities.…”
Section: Introductionmentioning
confidence: 99%
“…In several animal models, studies demonstrated that copaiba oil has healing and anti-inflammatory effects. Besides, anti-inflammatory and anti-tumor properties of copaiba oils have been described in several works [17][18][19][20].Those results are significant because they can the designed as applications to improve the quality of life in a society.…”
Section: Introductionmentioning
confidence: 99%